2020
DOI: 10.1186/s12889-020-8375-8
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers of managing patients with multiple chronic conditions in the community: a qualitative study

Abstract: Background: Approximately one-third of all adults worldwide are diagnosed with multiple chronic conditions (MCCs). The literature has identified several challenges facing providers and patients coping with managing MCCs in the community, yet few studies have considered their viewpoints in combination. A qualitative study involving healthcare providers and users was thus conducted to examine facilitators and barriers of managing patients with MCCs in the community in Singapore. Methods: This study involves 26 s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 53 publications
(67 reference statements)
0
44
0
Order By: Relevance
“…A study [ 18 ] found that experiences of patients with multiple long-term conditions are not different from patients with a single long-term disease. However, multi-morbidity is generally associated in the literature with poorer health outcomes [ 19 , 20 ], and providers face extra challenges when managing these patients [ 21 ]. This inconclusive evidence shows that more research looking at population-based studies is needed.…”
Section: Introductionmentioning
confidence: 99%
“…A study [ 18 ] found that experiences of patients with multiple long-term conditions are not different from patients with a single long-term disease. However, multi-morbidity is generally associated in the literature with poorer health outcomes [ 19 , 20 ], and providers face extra challenges when managing these patients [ 21 ]. This inconclusive evidence shows that more research looking at population-based studies is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficient management of CVR depends on the access to health services, qualified professional care, and self-care. 34 The quilombola communities face political and operational difficulties, since the nearest health services usually have inadequate infrastructure, limited and fragmented care, and few human and material resources. 35,36 Moreover, the adoption of healthy lifestyle habits also depends on the professional approach, which must consider the peculiarities of these individuals, including their beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Moreover, the adoption of healthy lifestyle habits also depends on the professional approach, which must consider the peculiarities of these individuals, including their beliefs. 34…”
Section: Discussionmentioning
confidence: 99%
“…What is particularly worrying is that many people have more than one chronic disease. Approximately one-third of all adults worldwide are diagnosed with multiple chronic diseases [2]. Multiple chronic diseases are de ned as two or more chronic diseases within one person in a speci c period of time [3].…”
Section: The Prevalence and Harm Of Multiple Chronic Diseasesmentioning
confidence: 99%